Preparation method of high-performance degradable nano composite aerogel material

By constructing a hybrid network framework of carbon nanotubes and nanocellulose on the surface of polylactic acid, high-performance degradable nanocomposite aerogels are prepared using Pickering emulsion technology and freeze-drying method, which solves the problem of difficulty in degradation of traditional aerogel materials and insufficient performance when applied in the field of oil-water separation.

CN119613803AInactive Publication Date: 2025-03-14JIANGSU OCEAN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411789182.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional aerogel materials are difficult to degrade, resulting in environmental pollution, and when used in the field of oil-water separation, it is difficult to obtain aerogel materials with uniform pore size and high mechanical strength.

Method used

Using Pickering emulsion technology, a hybrid network framework is constructed on the polylactic acid surface using carbon nanotubes and nanocellulose, and superhydrophobic, high-strength and excellent adsorption properties are prepared by freeze-drying.

Benefits of technology

It realizes the degradability and high performance of aerogel materials, has superhydrophobic, high strength and excellent adsorption properties, and is suitable for oil and soil treatment and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613803A_ABST
    Figure CN119613803A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance degradable nano composite aerogel material, which is characterized in that on the basis of a Pickering emulsion technology, nano cellulose is used as an emulsifier, a unique stereocomplex crystal structure of a degradable polylactic acid material is combined by virtue of a strong hydrogen bond between rich oxygen-containing functional groups on the surface of the nano cellulose and carbon nanotubes and a skeleton supporting effect, and the high-performance degradable nano composite aerogel material is prepared. The stereocomplex polylactic acid / nanocellulose / carbon nanotube nanocomposite aerogel is prepared based on a freeze-drying method, and the mechanical strength and the surface hydrophobic and oleophylic characteristics of the composite aerogel are enhanced by utilizing the high enhancement characteristic of nanocellulose and the regulation and control of aerogel crystallization and microporous structures by introducing stereocomplex crystals and carbon nanotubes; and high-efficiency oil-water separation is realized by utilizing the high adsorption characteristic of the composite aerogel meshes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-performance degradable polylactic acid nanocomposite aerogel material, belonging to the technical field of biodegradable materials and aerogel porous materials. Background Art

[0002] With the rapid development of industrialization, oil pollution has become a global environmental problem. Accidents such as oil spills, ship collisions, and oil pipeline ruptures have caused a large amount of oil to enter water bodies and soil, causing serious damage to the ecosystem, threatening biodiversity, and affecting human health and economic development. In the treatment of oil pollution, aerogels have attracted attention due to their unique physical properties. Aerogels are usually formed by removing the liquid in the gel, leaving a solid with a three-dimensional network structure. The structure of aerogels is similar to that of a sponge, with a large number of microscopic pores that occupy most of its volume, making it extremely light and having excellent adsorption properties. The characteristics of aerogels include ultra-low density, high specific surface area, excellent thermal insulation, good acoustic properties, and chemical stability. These characteristics make aerogels widely used in various fields. Although aerogels have many excellent properties and broad application prospects, they also face some challenges and problems. One of the most prominent problems is the difficulty of aerogels to degrade. Due to their special structure and composition, traditional degradation methods are not suitable for aerogels, and discarded aerogels may exist in the environment for a long time, which has a potential impact on the ecosystem. In order to solve this problem, developing degradable aerogel materials and exploring new degradation pathways such as biodegradation and photodegradation to reduce the negative impact of aerogels on the environment have become research hotspots.

[0003] Polylactic acid (PLA) is a biodegradable polymer formed by polymerization of lactic acid molecules. Its molecular structure contains carboxyl and ester bonds, which make it biocompatible and degradable. Polylactic acid has high strength, heat resistance and transparency, similar to many plastics, but has the advantage of biodegradability, so it is widely used in medical, packaging, textile and other fields. However, PLA itself also has certain defects, such as slow crystallization speed, easy collapse and rupture of bubbles when forming aerogel, which makes it difficult to obtain aerogel materials with uniform pore size and high mechanical strength, limiting its application in the field of oil-water separation. Chinese invention patent CN 109517212 A discloses a cellulose-graphene oxide-chitosan ternary composite aerogel, which is prepared by freeze-drying after oxidizing cellulose hydroxyl groups to aldehyde groups with sodium periodate and reacting with chitosan. The preparation process is complicated and inefficient. Since cellulose, chitosan and the like contain a large number of hydroxyl groups, the hydrophobicity of the composite aerogel is affected to a certain extent. Chinese invention patent CN 111167414 A discloses a grass-modified graphene aerogel for efficient oil-water separation and a preparation method thereof. Rye grass is used as a modifier and urea is used as a cross-linking agent. Grass-modified graphene hydrophobic aerogel is prepared by hydrothermal reaction and used for oil-water separation. However, the preparation process requires high temperature and high pressure combined with freeze drying, and the preparation process is complicated. In the current field of nanocomposite aerogel material technology, traditional preparation methods have many limitations. Most existing technologies are difficult to achieve precise control at the microstructure level, resulting in poor dispersion of the components inside the material and unsatisfactory interactions. Therefore, it is of great significance to prepare PLA aerogels with uniform microporous structure and efficient mechanical and adsorption properties. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a high-performance degradable nanocomposite aerogel material in view of the deficiencies in the prior art. The method is characterized in that, based on the Pickering emulsion technology, carbon nanotubes are used as nanofillers, nanocellulose is used as an emulsion stabilizer and a structural support unit, a hybrid network skeleton structure is constructed on the surface of poly (d-lactic acid), and then poly (l-lactic acid) and poly (l-lactic acid) are solution-blended to prepare a water-in-oil Pickering emulsion to improve the dispersibility of the carbon nanotubes in the system; on this basis, the emulsion is freeze-dried to obtain a high-performance degradable nanocomposite aerogel with super hydrophobicity, high strength and excellent adsorption performance, which can be used as an oil pollution treatment material.

[0005] The technical solution of the present invention is a method for preparing a high-performance degradable nanocomposite aerogel material, which is specifically implemented according to the following steps: Preparation of poly (D-lactic acid) / nanocellulose / carbon nanotube composite emulsion; Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel; Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel.

[0006] Furthermore, step (1) comprises: based on the surface chemical reaction, firstly preparing a carbon nanotube aqueous dispersion of a certain concentration, adding a certain amount of nanocellulose, and uniformly dispersing by ultrasonic dispersion, using Pickering emulsion technology, mixing a certain concentration of poly (d-lactic acid) solution and nanocellulose / carbon nanotube aqueous dispersion with a certain oil / water ratio to obtain a mixed solution, and using a high-speed emulsifier to emulsify and disperse the mixed solution under certain conditions to obtain a poly (d-lactic acid / nanocellulose / carbon nanotube) composite emulsion.

[0007] Preferably, in step (1), the solvent of the poly (d-lactic acid) solution is at least one of dichloromethane, 1-4-dioxane or dimethyl sulfoxide, the carbon nanotubes are one of conductive carbon nanotubes, carboxylated carbon nanotubes and hydroxylated carbon nanotubes, the concentration of the carbon nanotubes is 5-10 mg / mL, the nanocellulose is one of cellulose nanocrystals and cellulose nanofibers, the mass ratio of carbon nanotubes to nanocellulose is (1-5):(1-10), the ultrasonic dispersion time is 30-90 min, the water / oil ratio is 1:(3-7), and the emulsification time is 5-10 min.

[0008] Furthermore, in step (2), a solution blending method is used to prepare a stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel.

[0009] Preferably, in step (2), 50 to 90 parts of poly-L-lactic acid solution are added to the poly-D-lactic acid / nanocellulose / carbon nanotube composite emulsion, stirred in a water bath at 30 to 80 ° C for 30 to 90 min at a speed of 300 to 900 rpm, and the mixed solution is poured into a mold and cooled to obtain a stereocomposite poly-lactic acid / carbon nanotube / nanocellulose composite gel.

[0010] Preferably, the poly-L-lactic acid and poly-D-lactic acid both have a molecular weight of ≥6×10 4 g / mol high molecular weight polylactic acid.

[0011] Furthermore, in step (3), a stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel is prepared by freeze drying. Step (3) comprises: placing the stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel obtained in step (2) in a refrigerator at -40 to 0 °C for 6 to 12 hours, taking it out and thawing it at room temperature for 12 to 24 hours, and then freezing it again under the same conditions. The stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel frozen in the refrigerator is placed in a freeze dryer at -100 to -20 °C and dried at a pressure of 1 to 15 Pa for 12 to 48 hours to obtain a stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel.

[0012] The invention provides a method for preparing a high-performance degradable nano composite aerogel material.

[0013] The invention is based on Pickering emulsion technology, uses carbon nanotubes as nanofillers, uses nanocellulose as an emulsion stabilizer and a structural support unit, constructs a hybrid skeleton network on the surface of poly (d-lactic acid), prepares a water-in-oil Pickering emulsion, and improves the dispersibility of the carbon nanotubes in the system. Subsequently, poly (l-lactic acid) and the emulsion are solution-blended to prepare a nanocomposite gel. On this basis, the gel is freeze-dried to obtain a high-performance degradable nanocomposite aerogel with super hydrophobicity, high strength and excellent adsorption performance, which can be used as an oil pollution treatment material.

[0014] Compared with the prior art, the advantages of the present invention are as follows: 1. The present invention introduces Pickering emulsion technology into the field of aerogel preparation, uses nanocellulose as an emulsifier, and relies on its own unique interfacial stability to form a stable and ordered adsorption layer on the surface of the droplet, accurately controlling the size, shape and stability of the emulsion droplets, laying a good foundation for the subsequent microstructure regulation of the composite aerogel.

[0015] 2. The present invention combines nanocellulose, carbon nanotubes and degradable polylactic acid materials in an orderly manner, and utilizes the strong hydrogen bonding between nanocellulose and carbon nanotubes to construct a stable skeleton support structure, so that each component is evenly distributed and tightly combined in the aerogel, and phase separation or agglomeration is not likely to occur, thereby ensuring the stability and uniformity of the overall structure of the material, which is conducive to exerting the advantageous performance of each component, and this stable structure can maintain good performance under long-term use or under different environmental conditions.

[0016] 3. The present invention uses stereocomposite crystals and the interaction between the components to regulate the crystallization and microporous structure of aerogels. The structural regulation of traditional aerogels mostly relies on means such as templates or external physical fields. The present invention starts from the chemical structure and interaction inside the material, affects the arrangement of molecular chains through stereocomposite crystals, and combines the support and construction of pores by nanocellulose and carbon nanotubes to achieve more precise and effective regulation of the microstructure of aerogels, thereby achieving the purpose of optimizing performance.

[0017] 4. The stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel prepared by the present invention has a microporous structure, and the optimization of the pore structure by the characteristics of each component and the interaction makes it have a high specific surface area and porosity, thus showing good adsorption characteristics. This porous structure not only provides abundant sites for adsorption, but also ensures the rapid diffusion and transmission of substances during the adsorption process, further improving its performance in applications such as adsorption and separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The dispersion of composite emulsion prepared by ordinary blending method and Pickering emulsion method.

[0019] Figure 2 Actual pictures of polylactic acid composite aerogel and stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel.

[0020] Figure 3 The dispersion of carbon nanotubes in aerogel prepared by conventional blending method (a) and nanocomposite aerogel prepared by Pickering emulsion method (b). DETAILED DESCRIPTION

[0021] The present invention is further described below by means of specific examples. It should be noted that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make non-essential improvements and adjustments to the present invention based on the contents of the present invention described above. Example 1

[0022] A method for preparing a high-performance degradable nanocomposite aerogel material, comprising the following steps: (1) Preparation of poly (D-lactic acid) / nanocellulose / carbon nanotube composite emulsion: First, prepare a 5 mg / mL carbon nanotube aqueous dispersion, add an equal amount of nanocellulose to the carbon nanotubes, and ultrasonically disperse for 60 min. Mix well to obtain a nanocellulose / carbon nanotube aqueous dispersion. Further, a 10 mg / mL poly (D-lactic acid) dichloromethane solution and the nanocellulose / carbon nanotube aqueous dispersion are mixed with an oil / water ratio of 3:1 to obtain a mixed solution, and emulsify at 8000 rpm for 5 min using a high-speed emulsifier to obtain a poly (D-lactic acid) / nanocellulose / carbon nanotube composite emulsion.

[0023] (2) Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel: Poly(L-lactic acid) was added to poly(D-lactic acid) / nanocellulose / carbon nanotube composite emulsion at a mass fraction ratio of 1:1. The mixture was stirred in a water bath at 40 °C for 30 min at a speed of 400 rpm. The mixture was poured into a mold and cooled to obtain a stereocomposite polylactic acid / carbon nanotube / nanocellulose composite gel.

[0024] (3) Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel: The stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel was placed in a -20°C refrigerator and frozen for 8 h, then taken out and thawed at room temperature for 12 h, and then frozen again under the same conditions. The stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel frozen in the refrigerator was placed in a -80°C freeze dryer and dried at a pressure of 5 Pa for 24 h to obtain a stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel. The dispersion of CNTs inside the nanocomposite aerogel was significantly improved, with no obvious agglomeration phenomenon. The pore diameter was 9.2 μm and the water contact angle was 146.5 o The compression strength and compression modulus at 50% are 7.36 MPa and 41.74 MPa, and the adsorption capacity for organic solvents is about 20.8 g / g. Example 2

[0025] A method for preparing a high-performance degradable nanocomposite aerogel material, comprising the following steps: (1) Preparation of poly (D-lactic acid) / nanocellulose / carbon nanotube composite emulsion: First, prepare 8 mg / mL carbon nanotube aqueous dispersion, add nanocellulose in an amount equal to the carbon nanotubes, and ultrasonically disperse for 60 min. Mix well to obtain nanocellulose / carbon nanotube aqueous dispersion; further, a poly (D-lactic acid) 1-4-dioxane solution with a concentration of 10 mg / mL and the nanocellulose / carbon nanotube aqueous dispersion are mixed with an oil / water ratio of 4:1 to obtain a mixed solution, and emulsify at 8000 rpm for 8 min using a high-speed emulsifier to obtain a poly (D-lactic acid) / nanocellulose / carbon nanotube composite emulsion.

[0026] (2) Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel: Poly(L-lactic acid) was added to poly(D-lactic acid) / nanocellulose / carbon nanotube composite emulsion at a mass fraction ratio of 2:1. The mixture was stirred in a water bath at 80 °C for 60 min at a speed of 600 rpm. The mixture was poured into a mold and cooled to obtain a stereocomposite polylactic acid / carbon nanotube / nanocellulose composite gel.

[0027] (3) Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel: The stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel was placed in a -40°C refrigerator and frozen for 12 h, then taken out and thawed at room temperature for 24 h, and then frozen again under the same conditions. The stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel frozen in the refrigerator was placed in a -80°C freeze dryer and dried at a pressure of 1 Pa for 24 h to obtain a stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel. The dispersion of CNTs inside the nanocomposite aerogel was significantly improved, with no obvious agglomeration phenomenon. The pore diameter was 5.4 μm and the water contact angle was 143.2 o The compressive strength and compression modulus at 50% are 6.14 MPa and 40.89 MPa, and the adsorption capacity for organic solvents is about 17.6 g / g. Example 3

[0028] A method for preparing a high-performance degradable nanocomposite aerogel material, comprising the following steps: (1) Preparation of poly (D-lactic acid) / nanocellulose / carbon nanotube composite emulsion: First, a 5 mg / mL carbon nanotube aqueous dispersion was prepared, and an equal amount of nanocellulose to the carbon nanotubes was added, and the mixture was ultrasonically dispersed for 60 min and mixed evenly to obtain a nanocellulose / carbon nanotube aqueous dispersion. Further, a poly (D-lactic acid) dichloromethane solution with a concentration of 8 mg / mL was mixed with the nanocellulose / carbon nanotube aqueous dispersion and an oil / water ratio of 2:1 to obtain a mixed solution, which was emulsified at 8000 rpm for 10 min using a high-speed emulsifier to obtain a poly (D-lactic acid) / nanocellulose / carbon nanotube composite emulsion.

[0029] (2) Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel: Poly(L-lactic acid) was added to poly(D-lactic acid) / nanocellulose / carbon nanotube composite emulsion at a mass fraction ratio of 2:1. The mixture was stirred in a water bath at 60 °C for 90 min at a speed of 900 rpm. The mixture was poured into a mold and cooled to obtain a stereocomposite polylactic acid / carbon nanotube / nanocellulose composite gel.

[0030] (3) Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel: The stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel was placed in a refrigerator at -20°C for 12 h, taken out and thawed at room temperature for 12 h, and then frozen again under the same conditions. The stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel frozen in the refrigerator was placed in a freeze dryer at -80°C and dried at a pressure of 1 Pa for 48 h to obtain a stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel. The dispersion of CNTs inside the nanocomposite aerogel was significantly improved, and there was no obvious agglomeration phenomenon. The pore diameter was 13.4 μm and the water contact angle was 151.5 o The compressive strength and compression modulus at 50% are 6.88 MPa and 40.91 MPa, and the adsorption capacity for organic solvents is about 18.4 g / g.

[0031] The present invention provides a method for preparing a high-performance degradable nanocomposite aerogel material, wherein carbon nanotubes are used as nanofillers, nanocellulose is used as an emulsion stabilizer and a structural support unit, a hybrid skeleton network is constructed on the surface of poly(d-lactic acid) by using the Pickering emulsion technology, and an oil-in-water emulsion is prepared to improve the dispersibility of the carbon nanotubes in the system, and then poly(l-lactic acid) is mixed with the solution to prepare a nanocomposite gel; on this basis, the gel is freeze-dried to obtain a high-performance degradable nanocomposite aerogel with super hydrophobicity, high strength and excellent adsorption performance. The preparation process of the degradable nanocomposite aerogel is simple and feasible, has wide practicality and promotion value, and can be used in the fields of oil-water separation and environmental protection.

[0032] The above are all preferred embodiments of the present invention. For ordinary technicians in this technical field, without departing from the principle of the present invention, various equivalent modifications to the present invention belong to the protection scope of the claims attached to this application.

Claims

1. A method for preparing a high-performance degradable nanocomposite aerogel material, characterized in that: The preparation of the material mainly includes the following steps: Preparation of poly (D-lactic acid) / nanocellulose / carbon nanotube composite emulsion; Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel; Preparation of stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel.

2. The method for preparing a high-performance degradable nanocomposite aerogel material according to claim 1, characterized in that: Step (1) comprises: based on the surface chemical reaction, firstly preparing a carbon nanotube aqueous dispersion of a certain concentration, adding a certain amount of nanocellulose, and uniformly dispersing and mixing by ultrasonication, using the Pickering emulsion technology, mixing a certain concentration of poly (d-lactic acid) solution and a nanocellulose / carbon nanotube aqueous dispersion with a certain oil / water ratio to obtain a mixed solution, and using a high-speed emulsifier to emulsify and disperse the mixed solution under certain conditions to obtain a poly (d-lactic acid / nanocellulose / carbon nanotube) composite emulsion.

3. The method for preparing a high-performance degradable nanocomposite aerogel material according to claim 2, characterized in that: In step (1), the solvent of the poly (d-lactic acid) solution is at least one of dichloromethane, 1-4-dioxane or dimethyl sulfoxide, the carbon nanotubes are one of conductive carbon nanotubes, carboxylated carbon nanotubes and hydroxylated carbon nanotubes, the concentration of the carbon nanotubes is 5-10 mg / mL, the nanocellulose is one of cellulose nanocrystals and cellulose nanofibers, the mass ratio of carbon nanotubes to nanocellulose is (1-5):(1-10), the ultrasonic dispersion time is 30-90 min, the water / oil ratio is 1:(3-7), and the emulsification time is 5-10 min.

4. The method for preparing a high-performance degradable nanocomposite aerogel material according to claim 1, characterized in that: In step (2), a solution blending method is used to prepare stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gels with different mixing degrees and stereocrystal contents.

5. The method for preparing a high-performance degradable nanocomposite aerogel material according to claim 4, characterized in that: In step (2), the poly-L-lactic acid solution is added to the poly-D-lactic acid / nanocellulose / carbon nanotube composite emulsion in a mass ratio of (1-5):1, and stirred in a water bath at 30-80°C. The stirring time is controlled to be 30-90 min and the stirring speed is controlled to be 200-800 rpm to prepare a stereocomposite nano-mixed liquid, which is further poured into a mold for cooling to obtain a stereocomposite poly-lactic acid / carbon nanotube / nanocellulose composite gel.

6. The method for preparing a high-performance degradable nanocomposite aerogel material according to claim 1, characterized in that: In step (3), a freeze-drying method is used to prepare a stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel.

7. The method for preparing a high-performance degradable nanocomposite aerogel material according to claim 6, characterized in that: Step (3) comprises: placing the stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel obtained in step (2) in a refrigerator at -40 to 0°C for 6 to 12 hours, taking it out and thawing it at room temperature for 12 to 24 hours, and then freezing it again under the same conditions; placing the stereocomposite polylactic acid / nanocellulose / carbon nanotube composite gel frozen in the refrigerator in a freeze dryer at -100 to -20°C and drying it at a pressure of 1 to 15 Pa for 12 to 48 hours to obtain a stereocomposite polylactic acid / nanocellulose / carbon nanotube composite aerogel.

Citation Information

Patent Citations

  • Preparation method of cellulose-graphene oxide-chitosan ternary composite aerogel

    CN109517212A

  • Grass modified graphene aerogel for efficient oil-water separation and preparation method and application thereof

    CN111167414A

  • Modified three-dimensional fiber-based aerogel material and preparation method thereof

    CN103288416A

  • Preparation method of nanocellulose and polymer composite aerogel

    CN106117592A

  • Preparation method of high-hydrophobicity aerogel porous material

    CN110157034A